PENEGAKAN HUKUM DI INDONESIA UNTUK SI KAYA DAN SI MISKIN - Sufiyah, Putri Cahya (Fakultas Hukum Universitas Kadiri, 2020)
ABSTRACT The state of Indonesia is a state of law. People will definitely be punished if they are caught violating the applicable laws in the country. However, law enforcement is often considered unfair to some people. In Indonesia, the people tend to be divided into several social classes. Even though everyone has been guaranteed the right to get equal treatment before the law, the facts on the ground show that violators of the rule of law will definitely get punishment according to their social class. This is what makes the emergence of a term that